Calculation of the unit normal vector for wall shear stress in the lattice Boltzmann model. (15th March 2020) - Min, Li; Jingcong, Huang; Yang, Zhang; Yuan, Wang; Changsong, Wu; Lefeng, Qu
Highlights: A method for the calculation of unit normal vector needed in wall shear stress analysis is proposed for lattice Boltzmann model. This method can be completely incorporated in the voxelization process of computational domain. This method requires fewer input parameters and has a higher computational efficiency than the existing methods. Abstract: The pathology of aortic diseases is related to wall shear stress, which in the lattice Boltzmann method can be easily calculated using information for the unit normal vector of computational geometry. This paper proposes a method to calculate the unit normal vector. In comparison with the existing method, this approach requires a smaller number of input parameters and significantly reduces the computational cost. Tests on several geometries indicate that this method is a better choice from the viewpoint of accuracy and operability. Finally, the distribution of wall shear stress in a realistic aortic arch is obtained and found to agree with the conclusions of a previous study.